The Influence of Financial Literacy and Entrepreneurial Orientation on MSME Performance with Financial Management Behavior as A Mediation Variable - Sufnirayanti Sufnirayanti; Sri Wahyuni Zanra (CV Edujavare Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of the Indonesian economy and play a crucial role in promoting inclusive economic growth, employment generation, and poverty reduction. This study aims to analyze the effect of financial literacy and entrepreneurial orientation on SME performance with financial management behavior as a mediating variable. The research employed a quantitative approach using Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis with SmartPLS 4.0 software. A sample of 395 SME owners in Pekanbaru City, Riau was selected using purposive sampling technique. The results indicate that: (1) financial literacy has a positive and significant effect on financial management behavior; (2) entrepreneurial orientation has a positive and significant effect on financial management behavior; (3) financial management behavior has a positive and significant effect on SME performance; (4) financial literacy has a positive and significant effect on SME performance; (5) entrepreneurial orientation does not have a significant effect on SME performance; (6) financial management behavior partially mediates the relationship between financial literacy, entrepreneurial orientation, and SME performance. The implications of this study provide input for SME owners and policymakers in improving financial literacy capacity and strengthening entrepreneurial orientation to drive better business performance.